NEIGHBORING NATIONS IN TURMOIL: THE FALLOUT OF THE LIBYAN CRISIS - Bello, Ibrahim Suleiman; Musa, Fatima Adebayo (American Journal of Legal Practice (AJLP), 2023)
The 2011 Libyan uprising has had a significant impact on its North African neighbors, including arms proliferation, drugs, and human trafficking, militia and jihadist groups' activity, humanitarian crisis, and economic hardship. This article explores the impact of the Libyan crisis on its neighboring countries, using secondary data sources and Rosenau's Linkage Theory to analyze the crisis' effects on the region. The paper discusses the history of Libya and its independence from colonial powers, becoming a socialist state under Muammar al Qaddafi, and the Arab spring. The theoretical framework of James Rosenau's Linkage Theory is also examined, emphasizing the relationship between domestic politics and foreign policy. The article examines the factors that contribute to the prolonged Libyan Crisis and the impact on Algeria, Sudan, Tunisia, and Egypt. The paper recommends border guards, international cooperation, and general elections to address the ongoing Libyan Crisis. The article concludes that a united front represented by international cooperation is needed to resolve the Libyan crisis and its effects on the neighboring countries